Use of Extinguish Plus™ to Reduce Red Imported Fire Ants and Increase Northern Bobwhite Abundance - James W. Caldwell; Nova J. Silvy; Roel R. Lopez; Fred E. Smeins; Michael E. Morrow; Brian L. Pierce; Israel D. Parker (National Quail Symposium Proceedings, 2017)
Populations of northern bobwhite (Colinus virginianus) have been declining throughout Texas since at least the 1970s. The red imported fire ant (RIFA, Solenopsis invicta) was introduced from South America and reached Texas by the 1950s. Previous studies have documented the negative effects of RIFA on northern bobwhite populations through both direct predation and indirect reduction of small invertebrates. In 2013, 2014, and 2015, large areas (1,490 ha in 2013 and 2,380 ha in 2014 and 2015) of the 3,744-ha portion of the Attwater Prairie Chicken National Wildlife Refuge (APCNWR) in Colorado County, Texas, were aerially treated with Extinguish Plus™, a chemical pesticide and reproductive inhibitor that targets ants. Our study took place on APCNWR and our objectives included evaluation of the impacts of RIFA treatment on 1) RIFA abundance, and 2) northern bobwhite nest success and brood survival. We trapped, banded, and radiocollared northern bobwhites in areas treated and not treated with Extinguish Plus from May 2014 through August 2016. We also collected RIFA abundance data using baited Petri dishes on areas treated and nontreated areas during these periods. Treatment reduced RIFA presence on the refuge by 73.4% during 2014 and 2015, but did not reduce RIFA presence during 2016 possibly because of displacement of RIFA colonies due to heavy flooding on the refuge. We detected a difference (χ21 = 11,009, P = 0.0009) in the number of females sighted with and without broods between treated (19.5% F with broods) and nontreated areas (35.7% F with broods). We also found a difference (t12 = 2.51, P = 0.027) in mean number of chicks per brood sighted within treated (4.7) versus nontreated (9.3) areas for 2014 and 2014; but in 2016, we found no difference (t12 = 0.32, P = 0.754) in mean number of chicks per brood sighted within treated (7.7) and nontreated (8.4) areas, which was possibly due to extensive flooding in the nontreated area in April that destroyed most first nests. Our data suggested treatment with Extinguish Plus did not increase northern bobwhite abundance on the APCNWR during the 2014, 2015, and 2016 bobwhite nesting seasons. Our results differ from previous studies, possibly because of time since treatment and differences in environmental factors between treated and nontreated areas such as ecological site, vegetation composition, and predator abundance.
Keywords: colinus virginianus; northern bobwhite; brood survival; red imported fire ant; solenopsis invicta